2023
DOI: 10.1039/d3ta00602f
|View full text |Cite
|
Sign up to set email alerts
|

Vertical-cavity surface-emitting laser (VCSEL)-based ultrafast photonic sintering of solid oxide fuel cells (SOFCs): prospects for time-efficient/two-dimensional scalability to large-sized SOFCs

Abstract: 980 nm VCSEL illumination eliminates the organic additives and densifies the laminated multilayered SOFC NiO–YSZ|NiO–ScCeSZ|ScCeSZ|GDC|GDCscaffold in just 2.42 h compared to >100 h needed for the conventional thermal sintering process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…14 In our review paper, we specically address the durability issues associated with SOFCs, aiming to accelerate the commercialization of this versatile technology. [15][16][17][18][19] Fuel cell degradation occurs due to the gradual loss of intrinsic conductivity during operation or the formation of insulating phases. A research study demonstrated that the intrinsic conductivities of various ceramics employed in SOFCs also decline as the operation progresses.…”
Section: Introductionmentioning
confidence: 99%
“…14 In our review paper, we specically address the durability issues associated with SOFCs, aiming to accelerate the commercialization of this versatile technology. [15][16][17][18][19] Fuel cell degradation occurs due to the gradual loss of intrinsic conductivity during operation or the formation of insulating phases. A research study demonstrated that the intrinsic conductivities of various ceramics employed in SOFCs also decline as the operation progresses.…”
Section: Introductionmentioning
confidence: 99%